Thermodynamic characterization of two pilot spray dryers and evaluation of the effect of high molecular weight compounds on traditional and lactose-free dairy mixes - Silva, Cleuber Raimundo da (2017)
The objective of this work is to develop a mathematical model that allows for thermodynamically evaluating of spray dryers through mass/energy balance, to elaborate products from mixing of the milk and whey and to evaluate the effect of compounds with high molecular weight in the physicochemical properties and drying characteristics of traditional and lactose-free dairy mixes. For the thermodynamic characterization, it has been utilized spray dryers with atomizer pressure nozzle (evaporation capacity: 1 kg of water/h) and with atomizer disc (evaporation capacity: 20 kg of water/h). For elaboration of the dairy mix, there have been used lactic bases (lactose containing and non-lactose containing bases), elaborated from different proportions of milk and whey, maltodextrin, inulin and soluble corn fiber. The mathematical model has been validated for the evaluation of mass and energy losses and allowed to compare the efficiency between spray dryers with different designs. The increase in whey content in dairy mix and, especially, the application of the lactose hydrolysis reduced both the quality of the powders (color, glass transition temperature, hygroscopy, etc) and drying properties (stickiness, caking and increased energy expenditure for water evaporation). The addition of the compounds with high molecular weight had a positive effect on the physicochemical properties and the drying of the powders, being maltodextrin the most efficient compound.